Pengaruh Kombinasi Konsentrasi Daun Teh (Camellia Sinensis) dengan Asap Cair (Liquid Smoke) dan Lama Pengasinan Terhadap Kualitas Nilai Hu (Haugh Unit) dan Kemasiran Telur Asin - Ismaila A Kadir; Effendy Abustam (Jurnal Ilmu dan Industri Peternakan, 2013)
ABSTRACT. This study was conducted in March-April 2013. The research took place in laboratory of Live stock Products Technology, Faculty of Science and Technology, Alauddin State Islamic University of Makassar. This study aims to know the effect of tea leaves (Camellia sinensis) with liquid smoke (liquid smoke) and long marinating of HU (Haugh unit) and granular the quality salted eggs. Completely randomized design (CRD) with a general pattern 5x4 by 3 replications. Arrangement of treatments as follows: Factor A: combination of tea leaves + concentration of liquid smoke, 1. Tea leaves (0%) + liquid smoke (0%), 2. Leaf tea (10%) + liquid smoke (0%), 3. Tea leaves (0%) + liquid smoke (10%), 4. Leaf tea (20%) + liquid smoke (0%), 5. Tea leaves (0%) + liquid smoke (20%). Factor B: long salting, 1. (6 days), 2. (7 days), 3. (8 days), 4. (9 days). Data were analyzed by analysis of variance using a completely randomized design (CRD) consisting of 2 parameters of egg quality testing using the Least Significant Difference Test (LSD). Based on the results of analysis of variance showed that administration of a combination of the concentration of tea leaves (Camellia sinensis) with liquid smoke (Liquid smoke) may affect the value of granular while the effect on the value of long marinating HU (Haugh unit). Keywords: Tea Leaves, Liquid Smoke, Long Salting, Salted Egg Quality.